Evaluasi faktor-faktor yang mempengaruhi impor bungkil kedelai (SBM) sebagai pakan di Indonesia : Evaluation of Factors Affecting The Import of Soybean Meal (SBM) as Feed In Indonesia - Wijayanti , Rini; Ridla, Muhammad; Mutia, Rita (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
The increase in demand for feed impacts the availability of feed ingredients such as soybean meal (SBM), which is still 100% derived from imports. This study aimed to analyze the factors impacting the import of SBM as a crucial feed ingredient in Indonesia, offering insights for governmental policy-making. Secondary data spanning 2019-2022, encompassing SBM import quantities, price, and quality, were sourced from the Import Service Recommendation System. Additionally, annual feed production data were obtained from the Feed Directorate Information System, overseen by the Directorate General of Livestock and Animal Health, Ministry of Agriculture, Republic of Indonesia. SBM prices were sourced from World Bank online data. The dataset spanned four years (2019-2022), each comprising twelve months, with eight parameters under examination. Multiple linear regression was employed to evaluate the influence of independent variables including price upon arrival in Indonesia (USD), moisture content, protein content, crude fiber content, crude fat content, feed production, and the world price (USD) on the dependent variable of import volume. The results showed that all independent variables significantly affect the volume of SBM imports. Partially, variables like feed production, international prices, prices upon arrival in Indonesia, and moisture content have a significant and negative effect on SBM imports. The coefficient of determination shows that the independent variables explain 66.1% of the import volume of SBM. The study highlights critical factors influencing SBM imports in Indonesia. Effective policies addressing these factors could enhance the sustainability of the poultry farming industry. Key words: animal feed, import, linear regression, soybean meal